Glued-laminated timber from northern hardwoods: Effect of finger-joint profile on lamellae tensile strength. (15th February 2021) - Morin-Bernard, Alexandre; Blanchet, Pierre; Dagenais, Christian; Achim, Alexis
Highlights: Finger joint profile have a significant impact on tensile strength of jointed lamellae. Failure mode is highly dependent of the species and its anatomical features. Finger joint efficiency and wood failure are lower with hardwoods than with softwoods. Failure of full-size hardwood glulam beams initiates at a bottom finger joint. Abstract: Because of their availability, mechanical properties and distinctive appearance, there is a growing interest for the use of hardwood species in structural products such as glued-laminated timber. Previous work on bonding and structural grading of northern hardwoods has shown that white ash (Fraxinus americana L.), yellow birch (Betula alleghaniensis Britt.) and white oak (Quercus alba L.) are promising species for the manufacture of Canadian hardwood glulam. The objective of this study was to investigate the impact of the finger joint profile on the tensile strength of jointed hardwood lamellae. Tensile tests conducted on finger-jointed lamellae confirmed the possibility to achieve characteristic tensile strengths up to 36.4 MPa for white ash, 33.6 MPa for yellow birch and 35.8 MPa for white oak. One white ash and two yellow birch full-size beams were also manufactured using the most efficient finger joint profile and submitted to bending tests, achieving strengths of 47.0 and 41.6 MPa, respectively. The investigated species gave promising results suggesting they could be suitable for the manufacture of glued-laminated timber, although further research is required on hardwood finger-jointing to optimize the machining and gluing parameters and increase the joint efficiency.